Exploring Plant Tissue Culture and Steviol Glycosides Production in Stevia rebaudiana (Bert.) Bertoni: A Review - Sharma, Shilpa; Gupta, Swati; Kumari, Deepa; Kothari, Shanker Lal; Jain, Rohit; Kachhwaha, Sumita (Agriculture (Basel), 2023)
Stevia rebaudiana (Bert.) Bertoni, commonly called “sweet leaf” is a medicinally and industrially important plant known to be rich in zero-calorie natural sweetening compound(s) known as “steviol glycosides”. However, due to its poor seed germination and slow vegetative propagation, it has become rather difficult to meet the increasing global demand for Stevia-based products. Different biotechnological approaches have been developed over the past few decades to overcome these limitations and allow for mass propagation of the plant. Several protocols for in vitro organogenesis, callogenesis, and cell suspension cultures have been developed during the past few years. Apart from this, attempts have also been made to improve the production of steviol glycosides through nutrient manipulation, the use of elicitors, hairy root cultures, genetic transformation, and metabolic pathway engineering. Therefore, this review provides an up-to-date report on the applications of various biotechnological tools for mass propagation and enhanced steviol glycoside production, along with a detailed bibliometrics analysis. This review also highlights research gaps and future considerations that could be fruitful for the scientific community to delve deeper into the various unexplored aspects of the architecture and functionality of this natural sweetening plant.